2020
DOI: 10.1002/er.5380
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical research on p‐type doping two‐dimensional GaN based on first‐principles study

Abstract: By using first principles, the p-doping mechanism of two-dimensional GaN with buckled structure is discussed in detail under various doping configurations, including different doping elements, positions, and concentrations. The research implies that difference in electronegativity between three doping elements: Be, Zn, Mg and two-dimensional GaN results in a significant change in atomic structure and charge distribution. When Be, Zn, and Mg atoms are doped at Ga position, doping process in two-dimensional GaN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…8,24 In addition, the Broyden-Flecher-Goldfarb-Shanno (BFGS) algorithm under GGA-PBE functional is used to optimize structure. 8,10,25 To obtain an accurate GaN monolayer model, we use the wurtzite GaN model to intercept an atomic layer along the (0001) plane as a unit cell and then establish a 4 × 4 × 1 supercell with 32 atoms, where the lattice constant is a = b = 3.189 Å. 31 The modeling of the GaN double-layer whose supercell size is also 4 × 4 × 1 comes from previous studies.…”
Section: Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,24 In addition, the Broyden-Flecher-Goldfarb-Shanno (BFGS) algorithm under GGA-PBE functional is used to optimize structure. 8,10,25 To obtain an accurate GaN monolayer model, we use the wurtzite GaN model to intercept an atomic layer along the (0001) plane as a unit cell and then establish a 4 × 4 × 1 supercell with 32 atoms, where the lattice constant is a = b = 3.189 Å. 31 The modeling of the GaN double-layer whose supercell size is also 4 × 4 × 1 comes from previous studies.…”
Section: Models and Methodsmentioning
confidence: 99%
“…Although the PBE method does not consider the excited state and thus underestimates the band gap value, the calculation can still predict the trend of electronic properties of GaN monolayer before and after Cs adsorption 8,24 . In addition, the Broyden‐Flecher‐Goldfarb‐Shanno (BFGS) algorithm under GGA‐PBE functional is used to optimize structure 8,10,25 . To obtain an accurate GaN monolayer model, we use the wurtzite GaN model to intercept an atomic layer along the (0001) plane as a unit cell and then establish a 4 × 4 × 1 supercell with 32 atoms, where the lattice constant is a = b = 3.189 Å 31 .…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work function (φ) is used to evaluate the emission capability, and it is defined as: φ = E v ‐ E F , where E v and E F represent the vacuum level and Fermi level, respectively. [ 32 ] Therefore, in Figure a, we visually plot the E CBM , E VBM , and E v in the spin‐up and spin‐down GaN band structure, the Fermi level is represented by the purple dashed line. It can be clearly found that after TM atom doping, the vacuum level of GaN nanowires is significantly reduced, which means that their work function is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…There is no doubt that the first-principle is an effective tool to study the natural properties of a solid at the atomic or electronic level. [42][43][44][45][46] To study the vacancy effect, all calculations of GaN with the N-vacancy were calculated by the first-principles calculation, as implemented in the CASTEP code. 47,48 The interaction between ion core and the valance electron was treated by the ultrasoft pseudopotentials.…”
Section: Methodsmentioning
confidence: 99%